Специфіка сучасного англомовного мультимодального дискурсу - Макарук, Лариса Леонідівна; Makaruk, Larysa L. (Lesya Ukrainka Eastern European National University, 2014)
Статтю присвячено дослідженню сучасного англомовного мультимодального дискурсу. Окреслено низку причин, що зумовлюють потребу у всебічному дослідженні вербальних і невербальних засобів, які використовують у писемному дискурсі для реалізації комунікативних інтенцій. Проаналізовано ключові концепції, які уможливлюють поліаспектно розглянути специфіку вербальних і невербальних засобів, що функціонують в англомовному комунікативному просторі. Звернуто увагу на взаємозв’язок і взаємозалежність кількох лінгвістичних дисциплін (графічної лінгвістики, соціальної семіотики, візуальної лінгвістики, когнітивної лінгвістики, візуальної комунікації, лінгвістики тексту, комунікативної лінгвістики, теорії мультимодальності й мультимодальної комунікації), в межах яких розглядають вербальні й невербальні засоби комунікації. Схарактеризовано основні поняття, якими послуговуються під час аналізу мультимодального дискурсу. Висвітлено ключові ознаки та специфіку семіотичних ресурсів й модусу. Описано особливості мультимодального дискурсу, звернуто увагу на системно-функціональний підхід і проблеми оволодіння спеціальними навичками письма та читання, які потрібні кожній людини в цифрове століття. Виокремлено перспективні напрями подальших досліджень з урахуванням останніх комунікативних тенденцій, притаманних сучасному англомовному соціуму. This article deals with the investigation of English multimodal discourse. An outline is given of reasons for which it can be considered necessary to investigate verbal and non-verbal means used in written discourse for the implementation of communicative intentions. An analysis is made that focuses on multidimensional key theories, which make possible the study of the peculiarities of verbal and non-verbal means functioning in the English communicative space. Attention is also devoted to the interrelationship and the interdependence of several linguistic disciplines–graphic linguistics, social semiotics, visual linguistics, cognitive linguistics, visual communication, textual linguistics, communicative linguistics, multimodal theory and multimodal discourse–within which verbal and non-verbal devices are considered. The key concepts which are involved in considering multimodal discourse have also been described. Essential points and specifics relating to semiotic modes and resources have been explained, and distinctive features of multimodal discourse have been described. Some attention has been devoted to the systemic and functional approach to the investigation of multimodal discourse; it can also be applied to the problems related to literacy and to the writing skills which are necessary for all individuals in this digital age. Prospective approaches for further research have been pointed out, considering the latest communication trends which are inherent in the modern English-speaking world.
Keywords: мультимодальність; мультимодальний дискурс; вербальні й невербальні засоби; візуальна грамотність; системно-функціональний підхід; multimodality; multimodal discourse; verbal and non-verbal devices; visual literacy; systemic-functional approach